Product service system: A conceptual framework from a systematic review - Annarelli, Alessandro; Battistella, Cinzia; Nonino, Fabio (Journal of cleaner production, 2016)
This paper sets out to contribute to a critical theory debate through the presentation and use of a framework for the categorisation of literature linked to Product Service System (PSS). Moving from the analysis of literature we provide a conceptual structure depicting the current situation of literature dealing with the analysis of economic impact and environmental/social impact of Product Service System. Moreover, we provide a methodological structure, concerning methodologies and research purpose behind papers. Literature mainly agrees about PSS benefits, barriers, and partly also on drivers, but from the descriptive and thematic analysis what emerged is a lack of clarity about PSS and its main fields: it started as a topic closely connected with sustainability, but subsequently different fields have developed other terminologies and focuses of research, developing their own theoretical base and frameworks. Therefore, we have found a lack of interconnection among fields and subject areas. A critical aspect in current literature is about the analysis/evaluation of Product Service System performance: economic and environmental analyses should be updated with new methodologies and new perspectives (i.e. privileging an ex post perspective rather than an ex ante one). Furthermore, these analyses should be integrated in a unique tool, which would be essential in providing a complete perspective on the PSS phenomenon and its effects. Finally, we propose and discuss main future research directions, connected to the main current research streams: sustainability, Product Service System business models and collaborative consumption. •A conceptual structure is proposed to analyse PSS literature under a new perspective.•Different fields of research developed their own theoretical base about PSS.•There is a need for new empirical approaches in PSS's economic analysis.•Environmental analyses need to be integrated with economic and social aspects.